The effectiveness of core stability exercises on non-specific low back pain: a systematic review - Dar, Shahid Mohd; Muhardzi, Naim Muzaffar; Kamsan, Siti Salwana (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2024)
PURPOSE:This study reviewed the current evidence on the effectiveness of core stability exercises specifically for individuals suffering from back pain by examining various experimental studies, to assess the impact of core strengthening on pain relief and functional improvements.METHODS:A systematic search of electronic databases (PubMed, science direct and Pedro) was conducted to identify experimental studies, that investigated the effect of core stability exercises on back pain and functional independence among patients with nonspecificback pain. Pedro scale was used to assess the methodological quality of the included articles.RESULTS:Of the 350 studies identified, Titles and abstracts of 228 recorded studies were reviewed and 122 studies were excluded. Out of 106 articles, 101 full text articles were retrieved and assessed and evaluated according to inclusion and exclusion criteria. 20studies met the criteria included in qualitative synthesis. The findings from these studies indicate that core stability exercises significantly reduce pain intensity and enhance functional outcomes in patients with non-specific low back pain.CONCLUSION:This systematic review highlights the effectiveness of core stability exercises in managing non-specific low back pain. The results provide robust evidence supporting the incorporation of these exercises into treatment protocols for back pain, emphasizing the need for personalized exercise programs. Keywords:Core stabilization exercises, Nonspecific low back pain, Disability